Power, profits and payments for ecosystem services in Hilsa fisheries in Bangladesh: A value chain analysis. (October 2017) - Porras, Ina; Mohammed, Essam Y.; Ali, Liaquat; Ali, Md. Shahajat; Hossain, Md. Belayet
Abstract: Commitments for sustainable growth often look good on paper but are messy in the practice. The Government of Bangladesh shows huge initiative towards SDG 14 (conservation and sustainable use of marine resources) by establishing measures to improve the stock of hilsa fish in the country, thus ensuring the supply of a valuable and charismatic fish species. Initial reports of the measures are optimistic, suggesting larger sizes of fish caught across the seasons. Bigger hilsa fetches better prices – as high as US$25 per kilo in niche markets. It is conservation business with profits. Yet the costs of these regulations are falling squarely on the shoulders of small fishermen who are poor, uneducated and in permanent debt. The government offers a small in-kind payment for ecosystem service (PES) in the form of rice, which is good but does not compensate for the loss of revenues and household protein during bans. These small fishers have no bargaining power and no voice in the design of policies that affect them. A common problem in policy design is the lack of clarity of the markets they affect, especially if they are informal. This study uses value chain models to unpick the hilsa value chain. It study provides hard data and evidence on processes, power, and profit creation. This consultation can help policy makers design better strategies to re-govern markets in more inclusive ways and help to achieve Sustainable Development Goals commitments. Highlights: Detailed value chain analysis of the hilsa fish catch and trade in Bangladesh. Analysis of potential for inclusive Payments for Ecosystem Services for sustainable fisheries; Power analysis and review of market unbalances; Link to international agenda e.g. Sustainable Development goals. Proposals for adding value in inclusive ways that reduce poverty and improve ecosystems.